IMF Survey, Volume 36 Issue 09. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2007)
IEO on IMF exchange rate advice; GFSR: financial system risks and issues for regulators; good times in Belgium; Africa's oil exporters; outlook for Middle East and Central Asia; Caucasus and Central Asia:capital flows; lessons from a decade of crises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet